Solar retinal phototoxicity masquerading as self-inflicted handheld laser-induced lesions - Nghiem-Buffet, Sylvia; Gaudric, Alain; Cohen, Salomon Y. (American journal of ophthalmology case reports, 2020)
To report multimodal imaging of lesions due to the unprotected observation of the sun with an astronomical telescope, mimicking self-inflicted handheld laser-induced macular lesions. A 44-year old man was diagnosed with chronic central serous chorioretinopathy leaving a relative scotoma in his left eye, with visual acuity limited to 20/40. He complained of a sudden visual loss to 20/400. Fundus examination showed a yellowish discoloration of the fovea. Fundus autofluorescence pictures showed hyper-autofluorescent spots that were hyperfluorescent both on fluorescein and indocyanine-green angiography. Spectral-domain optical coherence tomography (SD-OCT) showed hyper-reflective foveal outer layers, and OCT-angiography showed dark areas at the choriocapillaris. Multimodal imaging was highly suggestive of self-inflicted handheld laser-induced lesions that were ruled out by the patient. He remembered having observed the sun during an astronomical session, looking for solar winds. The main astronomical telescope was protected by a specific filter, but the aiming side-telescope was incidentally not protected by any filter. The unprotected observation of the sun with an astronomical telescope may result in visual loss due to macular burns that may mimic self-inflicted handheld laser-induced lesions. This hypothesis should be searched before concluding denied self-injuries.